Respuesta :

Answer:

pH = -log[H+],  pOH=- log[OH-]

pH                        pOH                               [H+]               [OH-]

2.0                  14-2.0 =12.0                       10^(-2.0)      10^(-12.0)                        

14-9.0=5.0              9.0                              10^(-5.0)       10^(-9.0)                         

3                           14-3= 11                           10^(-3)              10^(-11)                          

14-11=3                     11                                 10^(-3)              10^(-11)                               

Answer:

Explanation:

H2O <--> H+ + OH-

[H+] * [OH-] = 10^(-14)

pH = -log [H+]

pOH = - log [OH-]\

pH + pOH = 14

using the above definitions:

pH                        pOH                        [H+]            [OH-]

2.0                       12.0                       10^(-2.0)      10^(-12.0)

5.0                        9.0                        10^(-5.0)      10^(-9.0)

3                           11                            10^(-3)         10^(-11)

3                           11                            10^(-3)          10^(-11)